STUDI TENTANG PEMBANGUNAN PELABUHAN CILAMAYA DITINJAU DARI ASPEK TEKNIS (Studi Kasus : Pelabuhan Cilamaya Karawang) - Yuwono, Yuwono; Sidad, Balya Farras (Departemen Teknik Geomatika ITS, 2017)
Cilamaya port is a commercial port located in Karawang regency. Currently the Port Cilamaya is still in the first stage of construction process. Information about bathymetry and sea bottom sediments is needed to support post-development shipping lines. This research aims to provide information about bathymetry and define the depth of shipping lines. This research was carried out on March - 2015 in Cilamaya port area. The data used for the research are sounding data recorded by Singlebeam echosounder Kongsberg EA400, tide data, and sediment sample of Cilamaya waters , and the data was processed using software Caris Hips and Sips 8.1, Surfer 12, AutoCad Land Desktop 2007 and ArcGIS 10.1. The results showed that Cilamaya waters of Cilamaya Port is categorized into shallow waters with the depth on survey location ranged from 0.615 m - 10.684 m. Sea bottom morphology was flat with average slope 0.76% and it was categorized flat to almost flat. Sea bottom sediments is dominated by muddy sand. shipping lanes currently used by general cargo (General Cargo) and tankers ship with DWT value (Death Weight Tonnage) 5000 with minimum depth of 6.1 m and width of 130 m. Shipping lane plans for container ship with 10000 maximum value of DWT (Dead Weight Tonnange) was required minimum depth of 10.3 m. To optimize shipping line planning required capital dredge for shipping line area which have a depth of less than 10.3 m.